2015
DOI: 10.1080/10255842.2015.1075012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial-thickness tear on loading capacities of the supraspinatus tendon: a finite element analysis

Abstract: Partial-thickness tears of the supraspinatus tendon frequently occur at its insertion on the greater tubercule of the humerus, causing pain and reduced strength and range of motion. The goal of this work was to quantify the loss of loading capacity due to tendon tears at the insertion area. A finite element model of the supraspinatus tendon was developed using in vivo magnetic resonance images data. The tendon was represented by an anisotropic hyperelastic constitutive law identified with experimental measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Consistent with this, Kong et al managed 81 patients with partial-thickness tears of the supraspinatus tendon conservatively and found that after 1 year of follow-up, only 13 patients showed tear expansion on MRI [ 10 ]. Furthermore, Engelhardt et al concluded, by means of a finite element analysis, that partial-thickness tears of less than 40% should be treated mainly with rehabilitation, while tears of more than 60% should be surgically repaired to restore shoulder strength [ 11 ]. Currently, most clinicians prefer to use surgical intervention in patients with tendon tears of greater than 50% [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, Kong et al managed 81 patients with partial-thickness tears of the supraspinatus tendon conservatively and found that after 1 year of follow-up, only 13 patients showed tear expansion on MRI [ 10 ]. Furthermore, Engelhardt et al concluded, by means of a finite element analysis, that partial-thickness tears of less than 40% should be treated mainly with rehabilitation, while tears of more than 60% should be surgically repaired to restore shoulder strength [ 11 ]. Currently, most clinicians prefer to use surgical intervention in patients with tendon tears of greater than 50% [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Due to the specific loading conditions and anatomical position, the supraspinatus tendon is the most frequently damaged soft tissue of the shoulder ( Martin et al, 1998 ; Lake et al, 2009 ; Palastanga et al, 2006 ), being susceptible to partial or full-thickness tears ( Andarawis-Puri et al, 2009 ; Engelhardt et al, 2016 ; Thunes et al, 2015 ). Massive rotator cuff injuries may necessitate the reattachment of the tendon to the bony insertion with sutures: different surgical options are available ( Mantovani et al, 2016 ) but, contrary to ACL repair, there is no consensus on a gold-standard management approach ( Quental et al, 2016 ; Mantovani et al, 2016 ).…”
Section: Modeling the Whole Bone-tendon Construct: Load Transfer Optimization And Orthopedic Related Questionsmentioning
confidence: 99%
“…This problem makes the volume of soft tissues approach zero, and thus, the accuracy decreases in FE simulations. According to the conventional study [10] that quantifies the injury caused by partial-thickness tears of the supraspinatus tendon, the injury begins at the insertion site. This supports that the error occurs on critical process zones.…”
Section: Hyperelasticitymentioning
confidence: 99%
“…However, the biomechanical mechanism still has not been clarified [2,7,8]. This study, which aims to identify the biomechanical mechanism of shoulder impingement syndrome, is essential in that supraspinatus tendon injury can lead to additional critical disorders such as rotator cuff [9][10][11][12] or superior labrum anterior to posterior (SLAP) tears [13][14][15]. Typically, shoulder impingement syndrome consists of both external and internal impingement syndromes.…”
Section: Introductionmentioning
confidence: 99%